Socioeconomic Demand Determinants for Domestic workers: The Case of Jordan - Oran, Ahmad; Al-Assaf, Ghazi; Al-satel, Rania (Jordan Journal of Economic Sciences, 2021)
The demand for domestic workers in Jordan has risen rapidly since the beginning of 1980’s. This study aims to identify the determinants that may affect the demand for domestic workers in Jordan for the period 2018-2019. The study employed the binary logistic regression model using qulaitative data.the model include several explanatory variables that are believed to influence the demand for domestic variables. The estimated results showed that the number of family members has a significant and positive impact on the presence of domestic worker with odds ratio 22 times, as it comes in the first place. Then second place comes to family income in terms of importance in the positive impact on the on the presence of domestic workers with odds ratio 18 times, while the transfers of workers in outside comes in the third place in importance and with a positive effect and odds ratio 6 times.The presence of children under the age of ten in the family and disabled individuals in the family appear to have a negative influenceon the demand for domestic workers, and which is ranked fifth in the negative impact on the demand for domestic workers.